Online Sales Colaboration With Traditional Market Traders in Improving Econimic Welfare in Gowa Regency, South Sulawesi - Supri; Tawe, Amiruddin; Rakib, Muhammad; Sulolipu, Andi Annisa (Nusantara Economics and Entrepreneurships Journals, 2025)
This research aims to analyze online sales collaboration with traditional market traders in Gowa Regency, South Sulawesi, and its impact on economic welfare. Along with the development of information technology, many traditional traders have difficulty competing with the modern market. Therefore, collaboration between traditional market traders and online sales platforms is considered an effective solution to increase competitiveness and income. The method used in this research is a qualitative approach with in-depth interviews with a number of traditional market traders and online sales platform owners. The research results show that this collaboration not only increases market access for traders, but also helps them understand broader consumer behavior. Merchants involved in this collaboration reported significant increases in sales turnover and customer satisfaction. In addition, this research also identifies challenges faced by merchants in adapting new technology, including a lack of understanding of digital marketing and limited access to technological tools. Therefore, training and mentoring are important to ensure the success of this collaboration. By strengthening trader capacity, economic welfare can increase sustainably. Overall, online sales collaboration with traditional market traders in Gowa Regency has proven to have a positive impact on economic prosperity. It is hoped that these findings can become a reference for local government policies in supporting digital transformation for the traditional trade sector.